Pengaruh Employee Engagement dan Work-Life Balance terhadap Kinerja Karyawan Kantor Pusat Bank SulutGo: bahasa indonesia - Sahe, Nasya; Wehelmina Rumawas; Tamengkel, Lucky (JURNAL ADMINISTRASI BISNIS, 2026)
This study aims to analyze the influence of Employee Engagement and Work-Life Balance on Employee Performance at Bank SulutGo Head Office. Using a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected through questionnaires distributed to 122 employee respondents from various work units. The research instrument consisted of 30 questions measuring three variables: Employee Performance (12 items), Employee Engagement (9 items using the UWES framework by Schaufeli & Bakker), and Work-Life Balance (9 items based on the dimensions of Greenhaus et al.). The research findings indicate that: (1) Employee Engagement has a significant positive effect on Employee Performance (H1 accepted); (2) Employee Engagement has a significant positive effect on Work-Life Balance (H2 accepted); (3) Work-Life Balance does not significantly affect Employee Performance (H3 rejected). The research model explains 44.8% of the variance in Employee Performance and 41.4% of the variance in Work-Life Balance. Employee Engagement is proven to be the dominant factor with a total effect of 0.656 on Employee Performance.